Movement Against the Congress Government and the Context of Emergency in Indian Politics - SK, Nasiruddin (Publica: Jurnal Pemikiran Administrasi Negara, 2025)
The most discussed chapter of Indria Gandhi’s political career is the imposition of Internal Emergency on 25 June 1975 across India. Mrs. Gandhi established her authority over the whole of India by imposing the Emergency. The main aims of this study that to explore the real reasons why Indira Gandhi imposed emergency. Various political analysts and leaders of congress-opposition parties have blamed Gandhi’s power politics as the for the imposition of Emergency. On the other hand, many have blamed the undemocratic nature of Indian politics at the time as the reason for Mrs. Gandhi’s imposition of Emergency. In order to explore the real reasons for the imposition of emergency, it is particularly necessary to discuss the nature of the anti-central government in India in the 1970s. because the anti-Congress-government movement in various states, later changed to anti-Indira movement. And the Emergency was the ultimate result of the anti-Indira movement.